Evaluation of Literary Texts Translation from Persian to Arabic Based on Carmen Garces Model - Iysa Motaghizadeh; Seyyed Ala Naghizadeh (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2017)
Translation evaluation is one of the methods of criticism that is used to determine the quality level of translated texts. Usually, after the texts have been translated, the editors are evaluating the translated texts. Therefore, the translator of translated texts must have sufficient control in both the source and the target languages so that in addition to editing the target text being able to evaluate it in terms of equivalence. In this research, we are trying to find out, based on the model of the evaluation of the translation of Mrs. Carmen Garces which is designed to assess the translation of literary texts in four levels (lexical, grammatical, discourse, and stylistic) using descriptive and analytical method; we will assess Arabic translation of the message of the leader of the revolution to the pilgrims of Hajj. One of the findings of this paper is that cultural differences between Farsi and Arabic languages and finding appropriate synonyms at vocabulary, and grammatical level based on these differences represent one of the most important challenges in the translation process. Similarly, examples such as adaptation, equivalents, an extension of vocabulary in the target language and using proper and general vocabulary, susceptibility from colloquial language are among most important challenges in this context.